Your answer would be 4.
If we substitute in x = -8 and y = -4 into the expression, we get:
![\frac{3(-8) - 4}{-4 - 3}](https://tex.z-dn.net/?f=%5Cfrac%7B3%28-8%29%20-%204%7D%7B-4%20-%203%7D)
This then becomes:
=
= 4.
I hope this helps!
Answer:
.
Step-by-step explanation:
Distance formula : Distance between points (a,b) and (c,d) is given by :-
![D=\sqrt{(d-b)^2+(b-a)^2}](https://tex.z-dn.net/?f=D%3D%5Csqrt%7B%28d-b%29%5E2%2B%28b-a%29%5E2%7D)
Distance between points
.
![D=\sqrt{(2\sqrt{3}-(-\sqrt{12}))^2+(-\sqrt{32}-(-4\sqrt{2}))}\\\\=\sqrt{(2\sqrt{3}+\sqrt{2\times2\times3})^2+(-\sqrt{4\times4\times2}+4\sqrt{2})^2}\\\\=\sqrt{(2\sqrt{3}-\sqrt{2^2\times3})^2+(-\sqrt{4^2\times2}+4\sqrt{2})^2}\\\\=\sqrt{(2\sqrt{3}+2\sqrt{3})^2+(-4\sqrt{2}+4\sqrt{2})^2}\\\\=\sqrt{(4\sqrt{3})^2+0}\\\\=4\sqrt{3}\text{ units}](https://tex.z-dn.net/?f=D%3D%5Csqrt%7B%282%5Csqrt%7B3%7D-%28-%5Csqrt%7B12%7D%29%29%5E2%2B%28-%5Csqrt%7B32%7D-%28-4%5Csqrt%7B2%7D%29%29%7D%5C%5C%5C%5C%3D%5Csqrt%7B%282%5Csqrt%7B3%7D%2B%5Csqrt%7B2%5Ctimes2%5Ctimes3%7D%29%5E2%2B%28-%5Csqrt%7B4%5Ctimes4%5Ctimes2%7D%2B4%5Csqrt%7B2%7D%29%5E2%7D%5C%5C%5C%5C%3D%5Csqrt%7B%282%5Csqrt%7B3%7D-%5Csqrt%7B2%5E2%5Ctimes3%7D%29%5E2%2B%28-%5Csqrt%7B4%5E2%5Ctimes2%7D%2B4%5Csqrt%7B2%7D%29%5E2%7D%5C%5C%5C%5C%3D%5Csqrt%7B%282%5Csqrt%7B3%7D%2B2%5Csqrt%7B3%7D%29%5E2%2B%28-4%5Csqrt%7B2%7D%2B4%5Csqrt%7B2%7D%29%5E2%7D%5C%5C%5C%5C%3D%5Csqrt%7B%284%5Csqrt%7B3%7D%29%5E2%2B0%7D%5C%5C%5C%5C%3D4%5Csqrt%7B3%7D%5Ctext%7B%20units%7D)
Hence, the correct option is
.